Relationship Marketing Stage of Development in Romanian Banking Industry - Alina Filip; Diana Maria Vrânceanu; Bogdan Georgescu; Daniela Elena Marinescu (Amfiteatru Economic Journal, 2016)
The paper emphasizes the relationship marketing stage of development within the banking industry in Romania, by identifying the extent to which business objectives and marketing strategies of companies are customer oriented. In order to achieve this aim a qualitative marketing research was conducted, by applying in-depth semi-structured interviews. The target group of the research consisted of nine banking companies, selected according to the market share, while the research participants were employees responsible for marketing, sales and customer relationship management activities. Due to respondents' expertise, during the interviews could be applied mixed research methods in the process of data collection and subsequently, in data analysis. According to research objectives and results, although there is an increase in the importance of customer orientation within banking policies, the integration of relationship marketing optics at the institutional management level is facing a number of deficiencies, especially with regard to the concerns about employees' satisfaction and loyalty or to the development of relationships with other stakeholders. The degree of satisfaction with the adoption of customer relationship management technology is relatively high among banks, being appreciated mainly those banking performance achieved in terms of retention rate, cross-selling and customer satisfaction. Most banks use the gross customer retention index as the main indicator of customer portfolio stability, although retention objectives tend to be set differently depending on customer value. Internal marketing strategies are developed around staff training processes, while performance evaluation criteria are rather specific to a transactional marketing approach. Results of the research provide clues on the relationship marketing processes and activities that need to be improved, in order to strengthen the current customer base and the competitive position in the banking industry.
Keywords: M31; 330; relationship marketing; customer relationship management; internal marketing; banking industry; customer orientation; customer retention